1968
DOI: 10.1126/science.160.3830.888
|View full text |Cite
|
Sign up to set email alerts
|

Agent of Disease Contracted from Green Monkeys

Abstract: An infectious agent obtained from patients who became ill after exposure to tissues of African green monkeys is viral in character. By electron microscopy, the agent appeared cylindrical, 90 to 100 nanometers in diameter, and 130 to 2600 nanometers in length. Cross-striations at 5-nanometer intervals and a core diameter of 45 nanometers were observed. The agent was completely resistant to the effects of the metabolic inhibitor 5-bromodeoxyuridine, which may mean that RNA is the genetic material. It was sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(36 citation statements)
references
References 1 publication
0
36
0
Order By: Relevance
“…Reprints of the original papers were sent to all the foreign institutions involved in the efforts to find the unknown agent of this new disease. Articles confirming the isolation and identification of the new virus were published by Kunz et al [4] and by Kissling et al [5] of the Centers for Disease Control and Prevention in 1968.…”
Section: The Discovery Of Marvmentioning
confidence: 99%
“…Reprints of the original papers were sent to all the foreign institutions involved in the efforts to find the unknown agent of this new disease. Articles confirming the isolation and identification of the new virus were published by Kunz et al [4] and by Kissling et al [5] of the Centers for Disease Control and Prevention in 1968.…”
Section: The Discovery Of Marvmentioning
confidence: 99%
“…Lipid: Lipid solvents destroy viral infectivity [10][11][12] and release a 1.32 g/cm3 RNP from the virions [9]. The percentage of virion lipid is unknown.…”
Section: A Properties O F the Virus Particlementioning
confidence: 99%
“…Density is »<1.14 g/cm3 in po tassium tartrate [9], Infectivity is quite stable at room temperature but is destroyed in 30 min at 60° [10]. Virus is inactivated by UV and gamma irradiation [13a, 13b] and by 1% for malin [10] and (3-propiolactone [12], Both vi ruses are inactivated by brief exposure to com mercial phenolic disinfectants [Lange et al, un published] and are very sensitive to lipid sol vents [10][11][12], Morphology: The virions of EBO and M BG are very similar in morphology, and the fol lowing general morphological description is derived from several sources [5,[14][15][16]. By electron microscopy, MBG and EBO particles are pleomorphic, appearing as long filament ous forms (sometimes with extensive branch ing) or as U-shaped, '6'-shaped, or circular forms.…”
Section: A Properties O F the Virus Particlementioning
confidence: 99%
See 1 more Smart Citation
“…Of 30 cases, 7 were fatal. Several reviews are available and are suggested for information on clinical and isolation findings (112,205,221,310,314,316). Serological studies attempting to determine what monkeys and apes may be responsible for spreading or harboring this agent has led to confusion.…”
Section: Reovirusesmentioning
confidence: 99%